Does highly cross-linked polyethylene wear less than conventional polyethylene in total hip arthroplasty? A double-blind, randomized, and controlled trial using roentgen stereophotogrammetric analysis. - Glyn-Jones, S; Isaac, S; Hauptfleisch, J; McLardy-Smith, P; Murray, D; Gill, H (2008)
A prospective double-blind, randomized, and controlled trial was conducted using roentgen stereophotogrammetric analysis; 54 total hip arthroplasty patients were randomized to receive either highly cross-linked polyethylene (HXLPE) or standard ultra-high-molecular-weight polyethylene (UHMWPE) liners. The 3-dimensional penetration of the liner was determined over 2 years. For the first 3 months, both polyethylene types had a rapid penetration rate (HXLPE: 0.22 mm, SD = 0.17 mm; UHMWPE: 0.21 mm, SD = 0.15 mm; P = .78). After 3 months, the HXLPE penetration rate (0.06 mm/y, SD = 0.06 mm/y) was significantly lower than the UHMWPE penetration rate (0.10 mm/y, SD = 0.07 mm/y; P = .04). The penetration in the first 3 months was probably caused by creep or bedding in; from 3 months onward, much of the penetration was probably caused by wear. We conclude that HXLPE has a 40% lower wear rate as compared with UHMWPE, suggesting that it will perform better in the long term.